A study of golden proportion in design structure of Malay woodcarving motifs / Sn Sharasayyidah Abdul Kadir - Abdul Kadir, Sn Sharasayyidah (Faculty of Education, 2014)
The legacy of woodcarving inheritance is passed through many generations until today, therefore, it is only logic to preserve and uphold such traditions. An aim to study on the golden proportion in structure design of Malay woodcarving motifs based on interpretations of Malay Aesthetic principles and elements is being applied the new motifs design to contemporary artwork which is the artwork and installation art. The artist's statement related with a master carver to create the new motif design with interpreting Malay aesthetic principles and elements in their work. Every each woodcarving that artist made has their own golden proportion. So in this finding want to study what is the golden proportion and find out it in three generation of wood carver that researcher choose to study such Wan Mustafa Wan Su, Azizul Ahmad, Jamalias Ismail and many more. . The findings structure motifs are vital in understanding the intricate artworks of woodcarving motifs. In Malay arts, each motif has its own meanings and interpretations especially in Awan Larat Philosophy and Abdullah Mohamed or Nakula statement of woodcarving symbolism. It should be used as guidelines by those who are related in the artwork fields such as the artist creating new design, thus giving meaning and depth to overall artwork, without sacrificing the unique Malay aesthetics and identity.